ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia periode 2008-2010) - LaksitaPutri, Iriena Maharani (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2012)
The value of the company is an investor perception to the company, which is often associated with the stock price. The higher the value, the higher the company’s shareholder wealth. One proxy of the value of the company is the Price to Book Value (PBV). PBV is the ratio of stock price to book value of the company. This study aimed to examine the effect of Debt to Equity Ratio (DER), Size, Earning to Growth Price to Book Value (PBV) and Return on Assets (ROA) as an intervening variable. Population of this study is all manufaturing firm listed on IDX during 2008-2010. By using purposive sampling, the written got 123 firm to be the sample. This study used path analysis technique and sobel test, in previously, the data was examined using classical assumption test. The results of this study for the first regression model showed that the variables jointly Debt to Equity Ratio (DER) and the size effect on the Return on Assets (ROA). For the second regression model showed that the variables jointly Debt to Equity Ratio (DER), size, Return on Assets (ROA) and Earnings Growth affect the Price to Book Value (PBV). Of this study also showed that the Return on Assets (ROA) has no mediating effect on the relationship between Debt to Equity Ratio (DER) to the Price to Book Value (PBV), but the Return on Assets (ROA) has a mediating effect on the relationship between size the Price to Book Value (PBV).